Minimally invasive repair of pectus excavatum by the Nuss procedure in Poland and worldwide – a summary of 25 years of history - Białas, Adam J.; Kempińska-Mirosławska, Bogumiła (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
In 1987, Donald Nuss performed the first minimally invasive repair of pectus excavatum (MIRPE). The aim of the study was to summarize the 25 years of performing this technique and analyze its modifications. The study was prepared using methods commonly used in historical research: descriptive, comparative, inductive and deductive methods. The history of the earliest Nuss operations and updated Nuss procedure was described. The most important modifications of the Nuss procedure were summarized: Miller, Hebra, Schaarschmidt, Hendrickson and Al-Assiri modifications. Polish input to Nuss procedure surgery was described as well.